Platform for Agrobiodiversity Research Statement made at the 13th Regular Session of the Commission on Genetic Resources for Food and Agriculture (CGRFA): Agenda Item 2.2 Climate change and genetic resources for food and agriculture - Platform for Agrobiodiversity Research (Platform for Agrobiodiversity Research, 2011)
I speak today on behalf of the Platform for Agrobiodiversity Research which, as many of you know, had the honor to participate and provide the moderator for the Information Seminar on Climate Change and Genetic Resources for Food and Agriculture on Saturday the 16th.